SATIRE POLITIK DALAM PERSPEKTIF DEMOKRASI: SATIRE POLITIK DALAM PERSPEKTIF DEMOKRASI - Shuyen, Shuyen; Budianto, Kun; Zalpa, Yulion (Jurnal Studi Ilmu Politik, 2024)
ABSTRACT This research examines Political satire in a Democracy Perspective (Case Study of the Lapor Pak Trans 7 Program). This study aims to find out how political satire on the Lapor Pak program is from a democratic perspective. With this type of qualitative research using a descriptive analysis approach with data sources obtained through draft regulations, books, journals, media, online news, and others. The results of this study are that there are several political satires in several episodes in the Lapor Pak program. And in the Lapor Pak program there are patterns and forms of political satire, namely feedback patterns carried out by the players to bring up political satire which is packaged in a comedic manner so that it provokes laughter from the audience and through this satire the community likes the Lapor Pak program because the community feels represented to convey What do people want to convey but the community cannot convey it. And political satire in the Lapor Pak program is a form of a democratic country and is part of democracy itself, namely freedom of expression and opinion. And included in positive propaganda which reminds officials that they have to do their job properly. Keywords:media,comedy,satire,democracy